Characterizing the Structure and Functions of Social Networks of Men Who Have Sex with Men in Ghana, West Africa: Implications for Peer‐Based HIV Prevention. (January 2018) - Maina, Geoffrey; Strudwick, Gillian; Lalani, Yasmin; Boakye, Francis; Wilton, Leo; Nelson, LaRon E.
Abstract : N/A: Men who have sex with men (MSM) in Ghana are at an increased risk of contracting HIV. Understanding the social networks of MSM may support the development of HIV prevention strategies for this unique population. This article explores the structure and function of the social networks of MSM from 22 focus groups drawn from two urban and one rural setting in Ghana. Gaining insights into the characteristics of these networks will allow health care providers to design HIV prevention efforts and increase access to these programs.